Qualitative and Quantitative Analysis of Different Rhodiola rosea Rhizome Extracts by UHPLC-DAD-ESI-MSn - Fabian Alperth; Ivana Turek; Sandra Weiss; Dietmar Vogt; Franz Bucar (MDPI AG, 2019)
Rhodiola rosea has been used in folk medicine as ethanolic macerates for a long time. This study aims to provide a quantitative and qualitative analysis and comparison of different ethanolic Rhodiola rosea rhizome macerates (35%, 70%, and 96% v/v) and accelerated solvent extraction (ASE) extracts prepared with 85% methanol, in order to shed light on the effectivity of different extraction methods. Extract samples were analyzed by UHPLC-DAD-ESI-MSn on a ZORBAX SB-C18 column (100 × 2.1 mm, 1.8 μm) with a mobile phase consisting of water + 0.1% formic acid and acetonitrile. Qualitative analysis lead to the tentative identification of 18 compounds: Two cyanogenic glycosides (rhodiocyanoside A, lotaustralin), three phenylethanoids (salidroside, viridoside, 2-phenylethyl-vicianoside), two procyanidin and catechin derivatives (epigallocatechin-epigallocatechin gallate, epigallocatechin-3-O-gallate), five phenylpropanoids (cinnamyl alcohol, rosarin, rosavin, rosin, cinnamyl-(6’-O-β-d-xylopyranosyl)-O-β-glucopyranoside), two monoterpene alcohols (rhodioloside E, rosiridin) and four flavonols (rhodionidin, rhodiosin, rhodionin, kaempferol). Quantity was determined for salidroside, cinnamyl alcohol and its three major glycosides (rosarin, rosavin, rosin), as well as three flavonols (rhodionidin, rhodiosin, rhodionin). Methanolic ASE proved to be the superior extraction method for different substance groups. For macerates, high ethanol content increased yield and lowered hydrolysis of glycosides during extraction, but ethanolic macerates still showed low reproducibility and high fluctuations in quantity of marker compounds salidroside and rosavins, as well as flavonols. Rhodiola rosea rhizomes of wild origins seemed to underly great variability in chemical composition dependent on grow site.